Essentials of Autopsy Practice Current Methods and Modern Trends - Rutty, Guy N. (Springer London : Imprint: Springer, 2006)
Essentials of Autopsy Practice: Current Methods and Modern Trends provides an update on the advances and developments in autopsy practice. This concise, well-referenced text consists of chapters that can be read independently of each other, in addition to forming a cohesive book, which can act as a laboratory manual or reference guide. It starts with a general subject related to death or death investigation and then proceeds through a series of related chapters which become more specialized, ending in a highly specialized chapter related to a specific type of injury. Each chapter brings together the world knowledge in the particular subject. Useful to both trainees and consultants in all specialty areas within pathology including forensic pathology, the book also serves as a guide to all those involved in death investigation i.e. nurses, lawyers, paramedics and police officers.